1996
DOI: 10.3402/tellusa.v48i1.11630
|View full text |Cite
|
Sign up to set email alerts
|

Polar lows in the Labrador Sea: A case study

Abstract: In this paper, we will describe our analysis of a polar low event that occurred in the Labrador Sea during the winter of 1992. As there are unfortunately no in-situ observations of this event, we will rely on satellite data as well as the high-resolution objective analaysis from the ECMWF to document the environment in which the low developed and the structure of the low itself. We will show that the polar low developed during a cold air outbreak that was precipitated by the passage of an intense synoptic-scal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…pressure system. Somewhat along those, lines Moore et al () argue that the interaction between the tropospheric polar vortex and surface circulation features is enhanced in regions of low tropospheric static stability where surface heating increases penetration depths of upper level circulation anomalies. Moore et al () reported that the anomalous warm winter of 2017 that saw record sea ice minimums accompanied reversal of surface winds and general motion departing from the normal anticyclonic activity over the Beaufort Sea.…”
Section: Discussionmentioning
confidence: 83%
“…pressure system. Somewhat along those, lines Moore et al () argue that the interaction between the tropospheric polar vortex and surface circulation features is enhanced in regions of low tropospheric static stability where surface heating increases penetration depths of upper level circulation anomalies. Moore et al () reported that the anomalous warm winter of 2017 that saw record sea ice minimums accompanied reversal of surface winds and general motion departing from the normal anticyclonic activity over the Beaufort Sea.…”
Section: Discussionmentioning
confidence: 83%
“…During the winter of 2017, this so‐called tropospheric polar vortex shifted northward and intensified relative to climatology (Figure b). The interaction between the tropospheric polar vortex and the surface circulation feature is enhanced in regions of low tropospheric static stability, that is, regions with reduced vertical temperature gradients that can occur due to surface heating, since this increases the penetration depth of upper level circulation anomalies (Moore et al, ). Figure also shows that tropospheric static stability throughout the Arctic was reduced during the winter of 2017 as compared to climatology.…”
Section: Resultsmentioning
confidence: 99%
“…A source of energy for these systems is thought to the large air-sea fluxes of heat and moisture that are often associated with them [Shapiro et al, 1987;Moore et al, 1996]. Recently, evidence has been presented that the development of polar lows in the Labrador Sea region often occurs in conjunction with upper-level potential vorticity anomalies [Moore et al, 1996;Pagowski and Moore, 2001]. These anomalies can interact with and intensify surface circulations through a mechanism first suggested by Kleinschimdt in 1951 [Hoskins et al, 1985].…”
Section: Introductionmentioning
confidence: 99%
“…Moist processes, in particular latent heat released by convection, have also been discussed as contributing to the formation and intensification of polar lows [Rasmussen, 1979;Emanuel and Rotunno, 1989]. A source of energy for these systems is thought to the large air-sea fluxes of heat and moisture that are often associated with them [Shapiro et al, 1987;Moore et al, 1996]. Recently, evidence has been presented that the development of polar lows in the Labrador Sea region often occurs in conjunction with upper-level potential vorticity anomalies [Moore et al, 1996;Pagowski and Moore, 2001].…”
Section: Introductionmentioning
confidence: 99%